Frequency of Helicobacter Pylori Infections and Its Association with Immune Thrombocytopenia in Patients Presenting with Dyspepsia in Tertiary Care Setting, Islamabad - Mujtaba, Mian Asif; Khan, Hareema Saeed; Azhar, Rimsha; Zulfiqar, Amina; Bukhari, Shoukat Hussain; Yousaf, Asia (Life and Science, 2025)
Objective: To determine the frequency of Helicobacter Pylori (H. Pylori) infection and its association with immune thrombocytopenia in patients presenting with dyspepsia symptoms.Study Design: Cross-sectional study.Place and Duration of Study. The study was conducted at the Department of General Medicine, Gastroenterology and Hematology, PIMS Islamabad, Pakistan, from 20th October 2019 to 20th April 2020.Methods. A total of 275 patients with the symptoms of dyspepsia were enrolled. All patients of either sex or any age with the signs and symptoms of dyspepsia presenting through Gastro/Medicine OPD, wards, and emergency and admitted to hospital were included in the study. Those addicted to alcohol, on drugs (NSAIDS, Steroids) without PPI cover, chronic renal failure, and pregnancy were excluded from the study. The primary outcome was to determine frequency of helicobacter pylori infection in dyspeptic patients in our local settings.Results: In this study, out of a total of 275 cases, females presented in dominance with 61% proportion. The average age of patients was 40 years, ranging from 44 to 95 years. The main presenting complaints were retrosternal burning (74.4%), bloating (65%), pain in the upper abdomen (49.6%), and water brash (37.9%). The frequency of helicobacter pylori infection confirmed on stool for helicobacter pylori antigen was (64.2%). 30.5% of patients have immune thrombocytopenia among those with stool for helicobacter pylori antigen positive.Conclusion: Our findings validate previous reports on the association of helicobacter pylori infection with dyspepsia. In our study a high proportion of patients (64.2%) were having helicobacter pylori infection. How to cite this:  Mujtaba MA, khan HS, Azhar R, Zulfiqar A, Bukhari SH, Yousaf A. Frequency of Helicobacter Pylori Infections and Its Association with Immune Thrombocytopenia in Patients Presenting with Dyspepsia in Tertiary Care Setting, Islamabad. Life and Science. 2025; 6(1): 81-86. doi: http://doi.org/10.37185/LnS.1.1.630